Knowledge concerning organ transplantation among inhabitants of the Kielce Region - Marcickiewicz, Izabela; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2014)
Introduction: Transplantations often save human health and life, and simultaneously evoke many medical and philosophical controversies. Aim of the research: An attempt to evaluate knowledge about organ transplantation among inhabitants of the Kielce Region, and to determine factors that affect the level of this knowledge, as well as the use of the information obtained in the promotion of organ transplantation in the region. Material and methods: The study was conducted during the period July–October 2010 and covered a group of 150 inhabitants of the Kielce Region: 96 females and 54 males, who were employees of various institutions. All of them were asked to complete an anonymous questionnaire. The results of the survey were statistically analysed (descriptive statistics). The method of a diagnostic survey was used, with the questionnaire technique. A questionnaire form was selected as a research instrument. Results : Based on the results of the study, it may be presumed that awareness of the problem of organ transplantation among the inhabitants of the Kielce Region is at a good level, and the majority of them show a positive attitude towards the transplantation of organs. Conclusions: In Kielce, since the promotional campaign ‘Transplantation is a second life’, the number of organ donations has increased. A variety of actions have been undertaken by associations and foundations engaged in the promotion of organ transplantation to expand and update knowledge of this problem in society.